Continuous Ketamine Administration Decreases Monocyte Count in Sepsis Patients in Intensive Care Units - Hartono, Ruddi; Jaya, Wiwi; Mayasari, Mayasari; Isngadi, Isngadi (Faculty of Medicine, Brawijaya University, 2023)
Background: Cytokines storm becomes the most common cause of mortality in sepsis patients treated in the intensive care unit (ICU). Cytokines storm is characterized by an excessive elevation in the immunocompetent cells, including monocyte. Ketamine, as a sedating agent, has immunosuppressive properties. This study was conducted to determine the effect of ketamine on monocyte count in septic patients in the ICU.Methods: This is a quantitative case-controlÂ study of 30 patients treated in the ICU. The study subjects were divided into control (n=15) and treatment (n=15) groups. The treatment group received ketamine HCl therapy at 0.3 mg/kg body weight/hour. The mean monocytes were counted at 0, 24, and 48 hours post-therapy. Data analysis used an independent sample t-test with Î±=5%.Result: Administration of ketamine therapy in septic patients treated in the ICU showed a decrease in the monocytes during observation from 0 to 48 hours post-therapy. Administration of ketamine at 48 hours had a significantly lower monocyte (5.21%) compared to control (7.67%) (p=0.012).Conclusion: Ketamine administration reduces the monocytes count in septic patients treated in the intensive care unit. Ketamine is expected to be a therapeutic option in sepsis patients.